Association between temporal summation and conditioned pain modulation in chronic low back pain: baseline results from 2 clinical trials. (8th November 2021) - Kong, Jiang-Ti; You, Dokyong Sophia; Law, Christine Sze Wan; Darnall, Beth D.; Gross, James J.; Manber, Rachel; Mackey, Sean
Abstract : Supplemental Digital Content is Available in the Text. In chronic low back pain, the modest association between temporal summation and conditioned pain modulation suggests that they approximate relatively independent physiological processes and supports independent assessment of both measures. Abstract: Introduction: Temporal summation (TS) and conditioned pain modulation (CPM) represent different aspects of central pain processing. Their relationship and differential performance within distinct body locations are not well understood. Objectives: To examine the association between TS and CPM in chronic low back pain and the influence of testing location on this relationship. Methods: We analyzed baseline data from 2 clinical trials on participants with chronic low back pain (n = 264; 47.3% female; mean age = 41 years, SD = 12; mean pain = 5.3/10, SD = 1.4). Measures used included questionnaires assessing pain and negative affect, phasic thermal TS at the hand (thenar) and the lower back (lumbar), followed by CPM that included a thermal testing stimulus (Heat-6, the temperature where pain rating is 6/10) and a cold-pressor conditioning stimulus. Nonparametric, proportional odds logistic regression was used to model thenar, and separately, lumbar TS, using CPM, Heat-6, negative affect, and demographics. Results: Our models revealed a small association (βs = 0.17, P = 0.01) between reduced CPM and heightened TS at both testing sites, regardless of demographics or negative affect. Conclusion: Results suggest a modest association between TS and CPM, irrespective of anatomical testing location, demographics, and negative affect. These findings will help improve the methodology and interpretation of TS and CPM measurement in clinical pain populations.